Diagnostic Accuracy of Ultrasonography in Detection of Molar Pregnancy Keeping Histopathology as Gold Standard - Amin, Mahnoor; Wahid, Ghazala; Ihtesham, Rabeea; Nasir, Fatima; Bashir, Faryal; Abdullah, Mahrukh (Journal of Postgraduate Medical Institute, 2025)
Objective: To determine the diagnostic accuracy of ultrasonography in detecting molar pregnancy, using histopathology as the gold standard. Methods: This cross-sectional validation study was conducted at the Department of Radiology, Hayatabad Medical Complex, Peshawar from 01 July 2024 to 01 January 2025. A total of 171 pregnant women in their first trimester presenting with vaginal bleeding were included. All participants underwent pelvic ultrasonography performed by an experienced radiologist with findings recorded based on predefined ultrasonographic criteria for molar pregnancy and confirmed by histopathology. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy of ultrasonography were calculated. Results: Molar pregnancy was detected on ultrasonography in 151 (88.3%) patients, whereas histopathology confirmed molar pregnancy in 161 (94.2%) cases. The sensitivity of ultrasonography in detecting molar pregnancy was 88.20%, specificity was 10%, PPV was 94.04%, and NPV was 5.00%. The overall diagnostic accuracy of ultrasonography was 83.63%, with a p-value of 0.863. Conclusion: Ultrasonography demonstrated high sensitivity and PPV for detecting molar pregnancy but had low specificity and NPV. While it remains a valuable initial screening tool, reliance on histopathology for definitive diagnosis is necessary to avoid misclassification. Further regional studies are recommended to refine ultrasonographic criteria and improve diagnostic precision.